DIGITAL TRANSCENDENT LEADERSHIP: A GROUNDED STUDY ON MADRASAH PRINCIPALS’ STRATEGIC AGILITY IN NAVIGATING THE MERDEKA CURRICULUM - Mus Mulyadi; Saifaldin Idris Onia (Nurul Jadid University, 2026)
This study explores the emergence of Digital Transcendent Leadership (DTL) as a novel paradigm for navigating the complexities of the Merdeka (Emancipated) Curriculum within Islamic formal schools (Madrasahs). Employing a Constructivist Grounded Theory approach involving twelve Madrasah principals across Indonesia, the research reveals that strategic agility in faith-based educational contexts is not merely a technical proficiency but a deeply anchored metacognitive process rooted in transcendence. The findings construct the core category of the